Hyperelastic phase-field fracture mechanics modeling of the toughening induced by Bouligand structures in natural materials. (October 2019) - Yin, Sheng; Yang, Wen; Kwon, Junpyo; Wat, Amy; Meyers, Marc A.; Ritchie, Robert O.
Abstract: Bouligand structures are widely observed in natural materials; elasmoid fish scales and the exoskeleton of arthropods, such as lobsters, crabs, mantis shrimp and insects, are prime examples. In fish scales, such as those of the Arapaima gigas, the tough inner core beneath the harder surface of the scale displays a Bouligand structure comprising a layered arrangement of collagen fibrils with an orthogonal or twisted staircase (or plywood) architecture. A much rarer variation of this structure, the double-twisted Bouligand structure, has been discovered in the primitive elasmoid scales of the coelacanth fish; this architecture is quite distinct from "modern" elasmoid fish scales yet provides extraordinary resistance to deformation and fracture. Here we examine the toughening mechanisms created by the double-twisted Bouligand structure in comparison to those generated by the more common single Bouligand structures. Specifically, we have developed an orientation-dependent, hyperelastic, phase-field fracture mechanics method to computationally examine the relative fracture toughness of elasmoid fish scales comprising single vs. double-twisted Bouligand structures of fibrils. The model demonstrates the critical role played by the extra inter-bundle fibrils found in coelacanth fish scales in enhancing the toughness of Bouligand-type structures. Synthesis and fracture tests of 3-D printed Bouligand-type materials are presented to support the modeling and complement our understanding of the fracture mechanisms in Bouligand-type structures.